(untitled) (Global Journal of Science Frontier Research, 2012)
The investigation into food qualities of six (6) newly bred β-carotene cassava namely; NR07/0427, NR07/0432, NR07/0326, NR07/0506, NR07/0497 and NR07/0499 of the National Root Crops Research Institute (NRCRI), Umudike, Nigeria using TMS 30572 as control was carried out. The chemical composition of the fresh roots to determine their carotenoid, moisture and starch contents was also carried out. Furthermore, the six of newly bred β-carotene cassava and the TMS 30572 (control) were processed into high quality cassava flours (HQCF) with which their physico-chemical properties were determined. The HQCF were also used in making 10% cassava bread, chin-chin, cakes, strips and salad cream and evaluated organoleptically. The result showed that the moisture contents of the fresh cassava roots ranged from 71.27% (TMS 30572) to 75.26% (NR07/0427) while the starch contents ranged from 11.69% (NR07/0427) to 29.16% (NR07/0499)